2012
DOI: 10.1155/2012/159807
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Recognition and Activation of the Innate Immune Response in Zebrafish

Abstract: The zebrafish has proven itself as an excellent model to study vertebrate innate immunity. It presents us with possibilities forin vivoimaging of host-pathogen interactions which are unparalleled in mammalian model systems. In addition, its suitability for genetic approaches is providing new insights on the mechanisms underlying the innate immune response. Here, we review the pattern recognition receptors that identify invading microbes, as well as the innate immune effector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 204 publications
(260 reference statements)
3
103
1
Order By: Relevance
“…Components of the main innate immune signaling pathways, such as the major pattern recognition receptors, key adaptor proteins (such as MyD88 and TNF receptor-associated factors in the TLR and IL-1R pathways), and the downstream transcription factors NF-B and AP1 are all found to be highly conserved among humans, mice, and zebrafish. This finding strongly implies that similar signal transduction mechanisms exist among the three species (28,29). Particularly, the mammalian essential kinases TAK1 and IKK complexes in the TLR and IL-1R signaling pathways display the most apparent orthologies in zebrafish (29), although functional data are not yet derived.…”
Section: Tgf-␤-activated Kinase 1 (Tak1) Is a Key Kinase In Mediatingmentioning
confidence: 97%
See 1 more Smart Citation
“…Components of the main innate immune signaling pathways, such as the major pattern recognition receptors, key adaptor proteins (such as MyD88 and TNF receptor-associated factors in the TLR and IL-1R pathways), and the downstream transcription factors NF-B and AP1 are all found to be highly conserved among humans, mice, and zebrafish. This finding strongly implies that similar signal transduction mechanisms exist among the three species (28,29). Particularly, the mammalian essential kinases TAK1 and IKK complexes in the TLR and IL-1R signaling pathways display the most apparent orthologies in zebrafish (29), although functional data are not yet derived.…”
Section: Tgf-␤-activated Kinase 1 (Tak1) Is a Key Kinase In Mediatingmentioning
confidence: 97%
“…Zebrafish (Danio rerio) is increasingly becoming a unique in vivo model system to study infectious, innate immune and inflammatory responses that can complement studies in mouse and human cell lines (27,28). Components of the main innate immune signaling pathways, such as the major pattern recognition receptors, key adaptor proteins (such as MyD88 and TNF receptor-associated factors in the TLR and IL-1R pathways), and the downstream transcription factors NF-B and AP1 are all found to be highly conserved among humans, mice, and zebrafish.…”
Section: Tgf-␤-activated Kinase 1 (Tak1) Is a Key Kinase In Mediatingmentioning
confidence: 99%
“…In acute cases, other signs may include ventral skin hyperemia and accumulation of red-colored ascitic fluid in the peritoneal cavity (33). E. tarda infection has been established as a model for studying microbial infection in zebrafish (34,35). We adopted this model to further investigate the function of zebTLR9 and zebTLR21 in mediating the antimicrobial activity of CpG-ODNs.…”
Section: Function Of Zebtlr9 and Zebtlr21 In Mediating Cpg-odn-inducedmentioning
confidence: 99%
“…4). In addition, to further understand the effects on the innate immune system, we analyzed the expression of genes coding for important cytokines and for signal mediators and transcription regulators previously demonstrated to be relevant to the immune response (van der Vaart et al 2012, Meijer et al 2014. Strikingly, our data showed that all the genes studied in this context were downregulated at 4 hpi, except ptpn6, cxcr3.1, cxcr4b, and irf5 (Fig.…”
Section: Zebrafish Larvae Treated With a High Dose Of Human Insulin Dmentioning
confidence: 74%